Formation properties of the chemical composition of groundwater in Qandil Valley basin - سلوم سندس; أحمد محمد; كنان جمال راعي (Latakia University Journal -Basic Sciences Series, 2023)
This research is concerned with a hydrogeochemical study of water from a selected group of wells in the Qandil Valley area. The study aims to determine the origin of this water for the optimal future planning of the uses of water resources in the area. During three distinct periods of the year 2020-2021, several samples were collected from nine different water wells that were chosen carefully to cover the whole area. Later on, the different samples were tested and chemical analyses were conducted for each one of them. After examining these results, it was found that the water samples are of atmospheric (continental) origin, in addition to the presence of some salts in it, the proportion of these salts have been then calculated which after has confirmed the main role of the infiltrative cycle in the formation of the chemical composition of groundwater in the area, the hydrogeochemical types prevailing in the subterranean slope of the area were also determined, and it was found that the types were manganese and sometimes limestone, and the marine influence on the origin of the chemical composition of this water was very small, and this could be evident in some areas near the sea, especially in the periods of excessive extraction of groundwater. Eventually, the groundwater of the research area could be characterized as bicarbonate-magnesium, and sometimes as calcareous, according to the "Piper" and "stiff" diagram.